2018
DOI: 10.1159/000485622
|View full text |Cite
|
Sign up to set email alerts
|

TREM-1 Contributes to Inflammation in IgA Nephropathy

Abstract: Background: Circulating IgA1-containing immune complexes (cIgA1) were shown to play important roles in IgA nephropathy (IgAN). They could induce the release of multiple inflammatory factors, including MCP-1 and IL-6, and elevated urinary inflammatory factors were also reported in patients with IgAN, which suggested that inflammation is a major contributor to kidney injury in IgAN. After the previous identification of the upregulated release of soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The activation of TREM1 signaling pathway would promote the release of multiple cytokines and chemokines, resulted in amplification of inflammatory responses [30]. Our previous studies found that IgA1-containing immune complexes from IgAN patients could upregulate the expression of TREM1 in cultured mesangial cells and elevated level of its soluble form (sTREM1) in the urine of IgAN patients was correlated with severe clinical and pathological manifestations [31, 32]. Besides, a recent study showed that the increase of TREM1 mRNA expression level in peripheral leukocytes of patients with Alzheimer’s disease was significantly correlated with the hypomethylation of the gene promoter [33].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of TREM1 signaling pathway would promote the release of multiple cytokines and chemokines, resulted in amplification of inflammatory responses [30]. Our previous studies found that IgA1-containing immune complexes from IgAN patients could upregulate the expression of TREM1 in cultured mesangial cells and elevated level of its soluble form (sTREM1) in the urine of IgAN patients was correlated with severe clinical and pathological manifestations [31, 32]. Besides, a recent study showed that the increase of TREM1 mRNA expression level in peripheral leukocytes of patients with Alzheimer’s disease was significantly correlated with the hypomethylation of the gene promoter [33].…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 could not only mediate sepsis-related kidney damage but also contribute to inflammation in IgA nephropathy, which has been detected by urinalysis 21 . sTREM-1 levels were also shown to be significantly increased in hemodialysis patients and positively correlated with CRP and TNF-α levels 22 .…”
Section: Discussionmentioning
confidence: 96%
“…TREM-1 is expressed in many kidney cells, including renal mesangial cells ( Zhao et al, 2018 ), tubular epithelial cells ( Maiese et al, 2019 ; Pan et al, 2021 ), and kidney macrophages ( Campanholle et al, 2013 ; Zhang et al, 2019a ; Zhang et al, 2019b ). TREM-1 is also expressed in endothelial cells ( Gibot et al, 2019 ), although the role of TREM-1 in renal endothelial cells is not very well known.…”
Section: Discussionmentioning
confidence: 99%